Pengaruh Self-efficacy dan Self-Management dalam Implementasi Layanan Bimbingan dan Konseling di SMP N di Kota Jambi - Rasimin, Rasimin; Yusra, Affan; Arizona, Arizona (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
These are the objectives of this study: 1) To determine the extent to which self-efficacy influences the implementation of guidance and counselling at SMP N in Jambi City; 2) To determine the extent to which self-management influences the implementation of guidance and counselling at SMP N in Jambi city, and 3) To determine the direct influence of self-efficacy and self-management on the implementation of guidance and counselling at SMPN in Jambi City. The research design utilized in this study was quantitative, with multiple linear regression analysis serving as the expo-facto statistical test design. This study's population consisted of school counsellors at the State Junior High School in Jambi city. As for the findings of this study: 1. The self-efficacy variable (X1) has no effect on school services (Y). It is evidenced by the results of 0.146 > 0.05 and t count -1.464< t in table 1; 2. There is an influence of the self-management variable (X2) on services in schools (Y), as evidenced by the results of 0.000< 0.05 and t count 4.360 > t in table 1.98; 3. There is a simultaneous effect of self-efficacy (X)1 and self-management (X2) on services in schools (Y), 0.000< 0.005. It indicates that variables have a simultaneous relationship